The role of extracellular vesicle miRNAs and tRNAs in synovial fibroblast senescence - Susanne N. Wijesinghe; James Anderson; Thomas J. Brown; Dominika E. Nanus; Bas Housmans; Jonathan A. Green; Matthias Hackl; Katie K. Choi; Kenton P. Arkill; Tim Welting; Victoria James; Simon W. Jones; et al. (Frontiers in Molecular Biosciences, 2022)
Extracellular vesicles are mediators of intercellular communication with critical roles in cellular senescence and ageing. In arthritis, senescence is linked to the activation of a pro-inflammatory phenotype contributing to chronic arthritis pathogenesis. We hypothesised that senescent osteoarthritic synovial fibroblasts induce senescence and a pro-inflammatory phenotype in non-senescent osteoarthritic fibroblasts, mediated through extracellular vesicle cargo. Small RNA-sequencing and mass spectrometry proteomics were performed on extracellular vesicles isolated from the secretome of non-senescent and irradiation-induced senescent synovial fibroblasts. β-galactosidase staining confirmed senescence in SFs. RNA sequencing identified 17 differentially expressed miRNAs, 11 lncRNAs, 14 tRNAs and one snoRNA and, 21 differentially abundant proteins were identified by mass spectrometry. Bioinformatics analysis of miRNAs identified fibrosis, cell proliferation, autophagy, and cell cycle as significant pathways, tRNA analysis was enriched for signaling pathways including FGF, PI3K/AKT and MAPK, whilst protein analysis identified PAX3-FOXO1, MYC and TFGB1 as enriched upstream regulators involved in senescence and cell cycle arrest. Finally, treatment of non-senescent synovial fibroblasts with senescent extracellular vesicles confirmed the bystander effect, inducing senescence in non-senescent cells potentially through down regulation of NF-κβ and cAMP response element signaling pathways thus supporting our hypothesis. Understanding the exact composition of EV-derived small RNAs of senescent cells in this way will inform our understanding of their roles in inflammation, intercellular communication, and as active molecules in the senescence bystander effect.